2014
DOI: 10.1111/efp.12124
|View full text |Cite
|
Sign up to set email alerts
|

Xyleborus glabratus attacks and systemic colonization by Raffaelea lauricola associated with dieback of Cinnamomum camphora in the southeastern United States

Abstract: Laurel wilt, caused by Raffaelea lauricola, is responsible for extensive mortality of redbay and other American members of the Lauraceae in the southeastern United States. Raffaelea lauricola is a mycangial symbiont of the redbay ambrosia beetle (Xyleborus glabratus), and the beetle and fungus were accidentally introduced from Asia. Branch dieback of camphortree (Cinnamomum camphora), an Asian member of the Lauraceae, has been occasionally observed in areas where laurel wilt has decimated redbay populations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…The beetles transport specific fungal symbionts from their natal galleries to newly established galleries in a storage organ termed a mycangium (Batra, 1963;Francke-Grosmann, 1963), but both can be kept in the laboratory on artificial media (Biedermann et al, 2009). A third reason is their importance: In recent years, several ambrosia beetle-fungus symbioses have developed outbreaks causing significant economic and ecological damages, and understanding the interactions between the beetle and the fungus has immediate scientific, economic and ecological implications (Fraedrich et al, 2008;Hulcr & Dunn, 2011;Eskalen et al, 2013;Fraedrich et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…The beetles transport specific fungal symbionts from their natal galleries to newly established galleries in a storage organ termed a mycangium (Batra, 1963;Francke-Grosmann, 1963), but both can be kept in the laboratory on artificial media (Biedermann et al, 2009). A third reason is their importance: In recent years, several ambrosia beetle-fungus symbioses have developed outbreaks causing significant economic and ecological damages, and understanding the interactions between the beetle and the fungus has immediate scientific, economic and ecological implications (Fraedrich et al, 2008;Hulcr & Dunn, 2011;Eskalen et al, 2013;Fraedrich et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…They develop vascular symptoms, but do not die, which is similar to the response of camphortree [33]. Notably, rare tolerance to laurel wilt has been selected in redbay, and there is hope that these selections could be used to re-establish this tree in the southeastern coastal plain [36,120].…”
Section: Hosts Of Laurel Wiltmentioning
confidence: 99%
“…During the early stages of the laurel wilt epidemic, Fraedrich et al [13,33] examined X. glabratus x redbay interactions. They indicated that initial attacks by the insect in healthy trees were aborted and that reproduction by the insect was not observed in such trees.…”
Section: Ambrosial Symbiosesmentioning
confidence: 99%
See 2 more Smart Citations